Loss of function mutations in PTPN6 promote STAT3 deregulation via JAK3 kinase in diffuse large B-cell lymphoma - Demosthenous, Christos (Oncotarget, 2015)
PTPN6 (SHP1) is a tyrosine phosphatase that negatively controls the activity of multiple signaling pathways including STAT signaling, however role of mutated PTPN6 is not much known. Here we investigated whether PTPN6 might also be a potential target for diffuse large B cell lymphoma (DLBCL) and performed Sanger sequencing of the PTPN6 gene. We have identified missense mutations within PTPN6 (N225K and A550V) in 5% (2/38) of DLBCL tumors. Site directed mutagenesis was performed to mutate wild type (WT) PTPN6 and stable cell lines were generated by lentiviral transduction of PTPN6(WT), PTPN6(N225K) and PTPN6(A550V) constructs, and effects of WT or mutated PTPN6 on STAT3 signaling were analyzed. WT PTPN6 dephosphorylated STAT3, but had no effect on STAT1, STAT5 or STAT6 phosphorylation. Both PTPN6 mutants were unable to inhibit constitutive, as well as cytokines induced STAT3 activation. Both PTPN6 mutants also demonstrated reduced tyrosine phosphatase activity and exhibited enhanced STAT3 transactivation activity. Intriguingly, a lack of direct binding between STAT3 and WT or mutated PTPN6 was observed. However, compared to WT PTPN6, cells expressing PTPN6 mutants exhibited increased binding between JAK3 and PTPN6 suggesting a more dynamic interaction of PTPN6 with upstream regulators of STAT3. Consistent with this notion, both the mutants demonstrated increased resistance to JAK3 inhibitor, WHIP-154 relative to WT PTPN6. Overall, this is the first study, which demonstrates that N225K and A550V PTPN6 mutations cause loss-of-function leading to JAK3 mediated deregulation of STAT3 pathway and uncovers a mechanism that tumor cells can use to control PTPN6 substrate specificity.